Ультрадисперсные алмазы детонационного синтеза как средство коррекции процессов пероксидации белков и липидов при злокачественном росте - Шугалей, И.В.; Дубяго, Н.П.; Львов, С.Н.; Красногорский, И.Н.; Балашов, Л.Д.; Васильев, А.Г.; Шагова, Д.А.; Долматов, В.Ю. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
Comparative investigation of nanodiamonds of detonation synthesis (NDs), ionole, being one of the most popular antioxidants, and doxorubicine traditionally used in antitumor therapy, upon some biochemical processes in red cells has been investigated. As the result of the performed investigations NDs may be treated as potential new antitumor medicine, stimulating antioxidant defence of the organism seriously destroyed by the tumor.